2019
DOI: 10.1002/jmv.25409
|View full text |Cite
|
Sign up to set email alerts
|

Variable sources of Bk virus in renal allograft recipients

Abstract: BK virus is the causative agent of polyomavirus‐associated nephropathy, a major cause of kidney transplant failure affecting 1%‐10% of recipients. Previous studies that investigated the viral source on the kidney recipient pointed that the donor is implicated in the origin of human polyomavirus BK (BKPyV) infection in recipients, but giving the low genetic variability of BKPyV this subject is still controversial. The aim of this study was to determine if BKPyV replicating in kidney recipients after transplanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…6 More interesting, from a clinical point of view, are our findings relating clinical manifestations to the various genotypes of other studies have previously suggested. 8,[16][17][18][19][20] The BKPyV infection in the transplant recipient could be a mixture of the reactivation of their own genotype and infection by some new genotype from the donor. However, there is a study that showed that donor-derived viral transmission is a more important mode of BKPyV infection than reactivation of the recipient's own latent virus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 More interesting, from a clinical point of view, are our findings relating clinical manifestations to the various genotypes of other studies have previously suggested. 8,[16][17][18][19][20] The BKPyV infection in the transplant recipient could be a mixture of the reactivation of their own genotype and infection by some new genotype from the donor. However, there is a study that showed that donor-derived viral transmission is a more important mode of BKPyV infection than reactivation of the recipient's own latent virus.…”
Section: Discussionmentioning
confidence: 99%
“…15 A donor origin of BKPyV in kidney recipients has been suggested, after demonstrating a correlation between the serostatus of the donor and BKPyV replication in the recipient. [16][17][18][19][20] Very few studies have investigated the distribution of BKPyV genotypes and the clinical implications of the various BKPyV genotypes. [20][21][22] The aim of this study was to investigate the epidemiology of BKPyV genotypes in kidney transplant recipients in Spain and the influence of the BKPyV genotypes on the virological and clinical characteristics of BKPyV infection in this population.…”
Section: Introductionmentioning
confidence: 99%
“…The highest incidences of BKPyV DNA detection and viral loads above 1E4 copies/ml are most commonly observed within 6 months posttransplantation, with a median detection time of 2 to 4 months (98,112,119,122). A recent study investigated the impact of pretransplantation seroreactivity of donor-recipient pairs on posttransplantation BKPyV viremia and BKPyVAN development (123), considering that BKPyV infection might originate from the kidney allograft (124) and that BKPyV seroreactivity correlates with BKPyV replication after transplantation (125). The pretransplantation donor BKPyV IgG level was associated with the recipient's BKPyV viremia and BKPyVAN development and was the strongest pretransplantation factor for viremia and BKPyVAN in multivariate analysis; the recipient's BKPyV seroreactivity was inversely associated with BKPyV viremia and BKPyVAN, but these results were nonsignificant (123).…”
Section: Dna Viruses Double-stranded Dna Virusesmentioning
confidence: 99%
“…Conversely, 71.4% of de novo JCV viruric KT patients received a graft from a JCV viruric donor. Literature regarding sources of polyomavirus in renal allograft recipients are scarce and conflicting [23,25,26]. Notwithstanding, the tendency is to accept that polyomavirus urinary viral shedding may be transmitted by the allograft.…”
Section: Discussionmentioning
confidence: 99%